Conceptualizing the impact of perceived organizational support and psychological contract fulfillment of employees paradoxical intentions of stay and leave - Saood Akhtar, Muhammad; Mohd Salleh, Lailawati; Hisham Ghafar, Nor; AhmedKhurro, Mansoor; Adal Mehmood, Sultan (International Journal of Engineering and Technology, 2018)
The article presents a comprehensive and detailed conceptual framework on the effects of employees’ perceived organizational support on their paradoxical intentions of leaving to and staying with the organization in Psychological Contract Perspective. This study anticipates proposing an applicable technique to examine empirically the interrelationships of employees’ perceived organizational support, psychological contract fulfillment, intention to stay and intention to leave.This paper proposes theory-based path model, and possible interrelationships of related constructs such that the future analysis would be based on related statistical methods may include structural equation modeling approach.Although numerous researchers have studied the broad topics of perceived organizational support and employees’ turnover intentions, none of those studies has explored the paradoxical and differential impact of perceived organizational support on the intentions of staying and leaving. The innovative propositions using psychological contract fulfillment lenses in the relationship of perceived organizational support with the intention to stay and intention to leave, as explained by psychological contract perspective of social exchange theory would be the originality of this paper and possible contribution to the body of knowledge.